An exceptional family: Ophiocordyceps‐allied fungus dominates the microbiome of soft scale insects (Hemiptera: Sternorrhyncha: Coccidae) - Gomez‐Polo, Priscila; Ballinger, Matthew J.; Lalzar, Maya; Malik, Assaf; Ben‐Dov, Yair; Mozes‐Daube, Neta; Perlman, Steve J.; Iasur‐Kruh, Lilach; Chiel, Elad (Molecular ecology, 2017)
Hemipteran insects of the suborder Sternorrhyncha are plant sap feeders, where each family is obligately associated with a specific bacterial endosymbiont that produces essential nutrients lacking in the sap. Coccidae (soft scale insects) is the only major sternorrhynchan family in which obligate symbiont(s) have not been identified. We studied the microbiota in seven species from this family from Israel, Spain and Cyprus, by high‐throughput sequencing of ribosomal genes, and found that no specific bacterium was prevalent and abundant in all the tested species. In contrast, an Ophiocordyceps‐allied fungus sp.—a lineage widely known as entomopathogenic—was highly prevalent. All individuals of all the tested species carried this fungus. Phylogenetic analyses showed that the Ophiocordyceps‐allied fungus from the coccids is closely related to fungi described from other hemipterans, and they appear to be monophyletic, although the phylogenies of the Ophiocordyceps‐allied fungi and their hosts do not appear to be congruent. Microscopic observations show that the fungal cells are lemon‐shaped, are distributed throughout the host's body and are present in the eggs, suggesting vertical transmission. Taken together, the results suggest that the Ophiocordyceps‐allied fungus may be a primary symbiont of Coccidae—a major evolutionary shift from bacteria to fungi in the Sternorrhyncha, and an important example of fungal evolutionary lifestyle switch.